KEMANDIRIAN PENYELENGGARA MENJELANG PEMILIHAN UMUM TAHUN 2024 (STUDI KASUS DI KOMISI PEMILIHAN UMUM KOTA PAGARALAM) - Manggar Azahra; Taufik Akhyar; Norma Juainah (Jurnal Prodi Ilmu Politik, 2023)
ABSTRACT This research discusses the Independence of Organizers Ahead of the 2024 Democratic Party (Case Study of the General Election Commission of the City of Pagaralam). This study aims to determine the Independence of the Organizers Ahead of the 2024 Democratic Party (Case Study of the General Election Commission of the City of Pagaralam). Data collection techniques obtained in this study were interviews, documentation and observation. Data analysis techniques in this study were processed through data reduction, data presentation and drawing conclusions or verification. And in this study using the rule of law theory with four dimensions which is also a reference in everything that is carried out by the General Election Commission ahead of the 2024 democratic party. The results show that the holding of elections at the General Election Commission of the City of Pagaralam is independent. This is shown by the independence of the Pagaralam City KPUD regarding the independence of organizing ahead of the 2024 democratic party, in the results of interviews and analysis during research and what about the preparations that have been made by the Pagaralam City KPU.